Distributed and cooperative control with applications to building HVAC systems - Long, Yushen (2017)
According to the environment programme report\cite{Sylvie09} published by the United Nations, buildings account for 40% of energy consumption and resources and one third of greenhouse gas emissions. Thus to improve the energy efficiency of buildings becomes more and more attractive. Heating, ventilation and air-conditioning (HVAC) system composes one third to half of building energy use\cite{AswaniM} so to optimize the energy efficiency of it is one of the most promising directions. To this end, developing energy-efficient control strategies for building HVAC systems is necessary for both economy and environment protection.